EFFECTIVENESS OF ACCOUNTING APPLICATION IMPLEMENTATION ON THE ACCURACY OF FINANCIAL REPORTING OF MSMES IN BOJONEGORO - Siti Nurul Hidayah; Dina Alafi Hidayatin; Nurul Mazidah; Hafidza Nash’ul Amrina (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This research aims to analyze the effect of the effectiveness of accounting application implementation on the accuracy of financial reporting for SMEs in Bojonegoro. The research background is based on the lack of trust among SME owners in using digital accounting due to concerns about the accuracy of financial reporting. On the other hand, SMEs need innovation to support their business development. Moreover, SMEs are one of the largest contributors to GDP in Indonesia in general and in Bojonegoro in particular. The method used is quantitative research with a causal associative approach. Data was obtained from 100 respondents who use the BukuWarung, Kledo, or LAMIKRO accounting applications. The data analysis technique used is simple linear regression through SPSS 25. The results show that the effectiveness of accounting application implementation has a significant positive effect on the accuracy of financial statements, with a regression coefficient of 0.352 and an R² of 0.206. This means that this research confirms that the use of accounting applications in SMEs can improve the accuracy of SME financial reporting.